Strategies for the selective volume sintering of ceramics. Issue 17 (7th August 2014) - Mühler, Thomas; Helsch, Gundula; Heinrich, Jürgen G.; Yao, Dongxu; Gräf, Stephan; Müller, Frank A.; Günster, Jens
Abstract